The Effect of Oketani Massage on Increasing Breast Milk Production in Lactating Mothers Aged 0-6 Months in Ciseureuh Purwakarta Area in 2024 - Armiyanti, (Jurnal Indonesia Sosial Sains, 2025)
Babies should be given safe breast milk from birth to six months of age, without any other food or drink except vitamins and medicines. Breast milk is the key to the survival of both mother and baby. Meanwhile, breastfeeding coverage in the Ciseureuh Purwakarta Region in 2024 is projected to be 51.7%. Based on the above background, it shows that there is still a low level of exclusive breastfeeding by mothers for their babies. The purpose of this study is to determine the effect of breast milk production on breastfeeding mothers aged 0-6 months in the Ciseureuh Purwakarta area in 2024. The population in this study includes all breastfeeding mothers with infants aged 0-6 months; the sample is divided into two groups, namely 20 respondents in the intervention group and 20 respondents in the control group. The Wilcoxon test obtained a p-value of 0.000 (p < 0.05), which means that there is a significant difference between the pre-test and post-test results. Therefore, it can be concluded that Oketani massage has an impact on breast milk production in breastfeeding mothers between 0-6 months old in the Ciseureuh Purwakarta area in 2024. There is an effect of Oketani massage on breastfeeding mothers aged 0-6 months in the Ciseureuh Purwakarta area in 2024. The study provides evidence-based support for scaling up this intervention to improve breastfeeding outcomes, particularly in regions with low exclusive breastfeeding rates. Future research should explore the long-term effects and cost-effectiveness of implementing Oketani massage programs in diverse healthcare settings.